4x^2-2+8-3(4x^2-2)+(-x^2+3x-2)
4x^2 -2+ 8 -12x^2 + 6 -x^2 + 3x -2
4x^2 -12x^2-2x^2 +3x -2+ 8+6 -2
-10x^2 +3x +10
write the simplified expression
4x^2-2+8-3(4x^2-2)+(-x^2+3x-2)
PLEASE PLEASE PLEASE
include all the steps if you can
3 answers
For a "good form" solution, you should include "=" signs in front of each new line
4x^2-2+8-3(4x^2-2)+(-x^2+3x-2)
= 4x^2 -2+ 8 -12x^2 + 6 -x^2 + 3x -2
= 4x^2 -12x^2 - x^2 +3x -2+ 8+6 -2
= -9x^2 +3x +10
notice I also caught your error in the 2nd last and last line
4x^2-2+8-3(4x^2-2)+(-x^2+3x-2)
= 4x^2 -2+ 8 -12x^2 + 6 -x^2 + 3x -2
= 4x^2 -12x^2 - x^2 +3x -2+ 8+6 -2
= -9x^2 +3x +10
notice I also caught your error in the 2nd last and last line
thank you!